The Early of Islam in Indonesia - Erwin Hafid (JICSA : Journal of Islamic Civilization in Southeast Asian, 2012)
there are many debates among Islamic scholars the exact date and people who bring Islam to Indonesia. This debate happened because there is no valid data to reconstruct the date of coming of Islam. On other side, the meaning of “Islam” differs between one scholar and others, for example; some scholars define it in formal definition as a person who converted Islam. Meanwhile, some of them defined it in sociology term as Islam community or society.There are four opinions about the people who came to introduce Islam to Indonesia. One of them assumed that Islam was brought by India people, the second one from Arab, the third one from Persia, and the last one who thought that Islam came from China.